Massively calcified aneurysm of the anterior communicating artery: an unsuccessful clipping attempt followed by successful pCONus2-assisted coil occlusion. Issue 4 (19th April 2021) - Haj, Amer; Schmidt, Nils Ole; Wendl, Christina; Schebesch, Karl-Michael
Abstract: We report the unique case of a 67-year-old female patient with an incidentally discovered massively calcified aneurysm of the anterior communicating artery. After interdisciplinary discussion, we decided to attempt clipping the aneurysm because interventional therapy did not seem feasible and anchoring a stent would also have been difficult because of the morphology of the aneurysm. The clipping attempt was unsuccessful because of the aneurysm's massive calcification with strong adherence to the sphenoid planum. The aneurysm was then successfully occluded using pCONus 2-assisted coiling. We illustrate this and consecutive procedures, and we reviewed the literature on aneurysm calcification.